Is longer really better? Results of a retrospective real-life cohort study evaluating the benefit of adding a weekly educational session to a traditional 8-week home-based pulmonary rehabilitation programme in people with COPD - Cécile Chenivesse; Olivier Le Rouzic; Jean-Marie Grosbois; Sarah Gephine; Sophie Peres (BMJ Open)
Objectives To evaluate the short-term and long-term benefits of adding a weekly educational session to a traditional 8-week home-based pulmonary rehabilitation (PR) programme in people with chronic obstructive pulmonary disease (COPD). Primary hypothesis was that 8 home-based supervised sessions will be equivalent to 16 home-based supervised sessions at both short- and long-term after PR.Design Retrospective cohort study conducted on prospectively collected real-life data, from January 2010 to December 2021.Setting FormAction Santé, Pérenchies France.Participants Eligible individuals were aged >18 years with a diagnosis of COPD and referred to the home-based PR programme by their respiratory physician. Participants were retrospectively divided into two groups (Gr 1, 8 PR sessions, n=759, and Gr 2, 8 PR sessions+8 educational sessions, n=262).Intervention All participants received an 8-week personalised home PR programme. A subgroup of participants received one additional supervised home session per week, including education and motivational support for daily physical activities and walking.Outcomes Health-related quality of life, dyspnoea, anxiety and depressive symptoms, fatigue and exercise tolerance were assessed at baseline (M0), at the end of PR (M2), and 14 months (M14) after M0.Results Baseline characteristics and assessments were similar between groups with an exception for long-term oxygen therapy (Gr1: 69.8% vs Gr2 53.0%, p<0.001) and noninvasive ventilation (Gr1: 38.6% vs Gr2: 29.8%, p=0.015). At M2 and M14, all the assessments were improved in both groups (p<0.01). At M2, the improvement in health status and exercise tolerance was higher in Gr 2 compared with Gr 1 (p<0.05). From M0 to M14, 90 (11.9%) participants and 29 (11.1%) participants died in Gr 1 and Gr 2, respectively (p=0.794).Conclusion People with COPD benefited, at short and long terms, from both 8 or 16 supervised home-based PR sessions. Once-weekly home-based supervised sessions during 8 weeks, combined with unsupervised physical training sessions and self-management plan for the other health behaviours, might be the best compromise between patients, health professionals and policy makers.